Nanoparticle based periodontal drug delivery - A review on current trends and future perspectives - Amani Mohammed Basudan (Elsevier, 2022)
Introduction: Periodontitis is a chronic inflammatory disease, resulting due to host immune response against subgingival biofilm. Most conventional treatment protocols aim to control the subgingival biofilm by mechanical means, such as dental scaling and root planning, and frequently accompanied by antibacterial co‐adjuvant therapies, including antibiotics, antiseptics, or probiotics. Local drug delivery facilitates administration of a lower dose of the drug to the target site, but at higher concentration, thereby reducing systemic adverse effects and toxicity. The present systematic review was conducted with the aim of identifying and reporting nanoparticle based periodontal drug delivery systems, with a specific focus on current trends and future perspectives in this field. Materials & methods: Comprehensive literature search, restricted to published reports in English language between January 2000 and February 2022, was done electronically and manually. Search queries were addressed to the following electronic databases including, PubMed (MEDLINE), Science Direct (Elsevier), Cochrane Library, Web of Science (Clarivate Analytics) and Scholar (Google). Database search returned 780 results which were screened based on title, author names and publication dates, to identify 13 studies fulfilling the review criteria. Results: Data from the 13 included studies were reviewed and tabulated, elaborating the type of nanoparticle used, drug delivered and tissues/cells/subcellular components targeted by periodontal drug delivery. While majority of the studies were conducted in vitro, there were 3 in vivo studies and 3 clinical studies. Using nanotechnology for drug delivery resulted in better inhibition of bacterial growth, inflammatory modulation favoring resolution of periodontitis and capability for early tissue regeneration. Conclusion: Recent developments in nanotechnology have enabled targeted local delivery of drugs and anti-inflammatory biomolecules, in synergy with nanoparticles, towards periodontal pathogens, inflammatory cells and periodontal tissues. Further research evaluating clinical periodontal disease management through nanoparticle based local drug delivery drugs is highly recommended.